2020
DOI: 10.1186/s13223-020-0415-5
|View full text |Cite
|
Sign up to set email alerts
|

Food allergy among university students: uncharted territory

Abstract: Background: Food allergy is a growing global health concern, with limited studies conducted in developing countries. High-risk behavior regarding allergies is common among young adults, making them prone to severe allergic reactions. This study aimed to estimate the prevalence of food allergies among Imam Abdulrahman Bin Faisal University (IAU) students and to determine the rate of high-risk behaviors in this group.Methods: An online survey was conducted among IAU students enrolled between the academic years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…To outline the gaps that exist, we look to one such study that attempted to remedy this. This was a survey-based cross-sectional study of food allergy at Imam Abdulrahman Bin Faisal University (IAU), with 5497 students surveyed regarding presence or absence of allergy, and age of onset of food allergy if applicable [22]. This revealed that amongst those with a positive history for food allergy (174 students with clinically diagnosed food allergy of the 526 students who had a positive screening history), 51.7% developed allergy before the age of 14; with adolescent (29.1%) and adult development (19.2%) being less common [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To outline the gaps that exist, we look to one such study that attempted to remedy this. This was a survey-based cross-sectional study of food allergy at Imam Abdulrahman Bin Faisal University (IAU), with 5497 students surveyed regarding presence or absence of allergy, and age of onset of food allergy if applicable [22]. This revealed that amongst those with a positive history for food allergy (174 students with clinically diagnosed food allergy of the 526 students who had a positive screening history), 51.7% developed allergy before the age of 14; with adolescent (29.1%) and adult development (19.2%) being less common [22].…”
Section: Introductionmentioning
confidence: 99%
“…This was a survey-based cross-sectional study of food allergy at Imam Abdulrahman Bin Faisal University (IAU), with 5497 students surveyed regarding presence or absence of allergy, and age of onset of food allergy if applicable [ 22 ]. This revealed that amongst those with a positive history for food allergy (174 students with clinically diagnosed food allergy of the 526 students who had a positive screening history), 51.7% developed allergy before the age of 14; with adolescent (29.1%) and adult development (19.2%) being less common [ 22 ]. This aptly summarizes the relatively large proportion of patients developing food allergy at an adult age, but as with many other studies it fails to outline specific details regarding adult-onset allergy, including reaction and culprit food.…”
Section: Introductionmentioning
confidence: 99%
“…To outline the gaps that exist, we look to one such study that attempted to remedy this. This was a survey-based crosssectional study of food allergy at Imam Abdulrahman Bin Faisal University (IAU), with 5497 students surveyed regarding presence or absence of allergy, and age of onset of food allergy if applicable (22). This revealed that amongst those with a positive history for food allergy (174 students with clinically diagnosed food allergy of the 526 students who had a positive screening history), 51.7% developed allergy before the age of 14; with adolescent (29.1%) and adult development (19.2%) being less common (22).…”
Section: Introductionmentioning
confidence: 99%
“…This was a survey-based crosssectional study of food allergy at Imam Abdulrahman Bin Faisal University (IAU), with 5497 students surveyed regarding presence or absence of allergy, and age of onset of food allergy if applicable (22). This revealed that amongst those with a positive history for food allergy (174 students with clinically diagnosed food allergy of the 526 students who had a positive screening history), 51.7% developed allergy before the age of 14; with adolescent (29.1%) and adult development (19.2%) being less common (22). This outlines the relatively large proportion of patients developing food allergy at an adult age, but as with many other studies it fails to outline speci c details regarding adult-onset allergy, including reaction and culprit food.…”
Section: Introductionmentioning
confidence: 99%
“…This was a survey-based cross-sectional study of food allergy at Imam Abdulrahman Bin Faisal University (IAU), with 5497 students surveyed regarding presence or absence of allergy, and age of onset of food allergy if applicable (22). This revealed that amongst those with a positive history for food allergy (174 students with clinically diagnosed food allergy of the 526 students who had a positive screening history), 51.7% developed allergy before the age of 14; with adolescent (29.1%) and adult development (19.2%) being less common (22). This aptly summarizes the relatively large proportion of patients developing food allergy at an adult age, but as with many other studies it fails to outline speci c details regarding adult-onset allergy, including reaction and culprit food.…”
Section: Introductionmentioning
confidence: 99%